Pengaruh Manajemen Keuangan dan Mekanisme Corporate Governance Terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Terdaftar pada BEI 2018-2022 - Octanita Dewi, Alfina; Khairunnisa, Khairunnisa; Syahriandy, H. (Economic Reviews Journal, 2024)
This study aims to examine the impact of financial management and Corporate Governance Mechanisms on the financial performance of manufacturing companies listed on the IDX between 2018-2021. The sampling process through purposive sampling method, 73 companies were selected in 3 years, with 37 research samples. The results show the significance of Financial Management (0.000 < 0.05) and Corporate Governance (0.020 < 0.05), confirming their influence on financial performance. The F test also corroborates these findings with a Sig value (0.000 < 0.05), indicating that financial management and Corporate Governance together have a significant effect on the company's financial performance. Thus, this study provides a deeper understanding of the importance of financial management and Corporate Governance in improving the financial performance of manufacturing companies.